Improving dementia patient quality of life (QoL) by utilizing augmented reality mobile application - Engku Mat Nasir, Engku Mohd Nasri (2018)
Dementia illness defines as a condition where the patient lost the ability to recall memory entirely. Thus, many researchers have experiment developing new alternatives to cure dementia illness. This research proposed a new alternative treatment utilizing Augmented Reality (AR) technology based on home based treatment daily activities. The proposed alternative treatment is not meant to cure, nevertheless is to enhance dementia patient's quality of life (QoL). The AR system generates a vitiual object in the real world using marked AR system to project three-dimensional images in the patient sight or display panel. The task for each scenario classified based on home treatment activities that focus on the patient's daily activity. The displayed scenario facilitated patient to complete that particular task. The proposed system aid the patient by displaying video guide instructions. From the result, the proposed method able to reduce the degrading memory function effect based on time between 38% up to 57% for a limited short term depending on the given task. As a conclusion, the application can be further improve in term of display device's weight, detection accuracy, information quality and patient specific task. The application will be act as an alternative treatment for dementia patient and a foundation research for other similar memory function challenges disease (Alzheimer disease (AD)).